Bio-protective effects of Lactobacillus plantarum subsp. plantarum against aflatoxin b1 genotoxicity on human blood lymphocytes: a native probiotic strain isolated from Iranian camel milk - Parvaneh Afshar; Leila Roozbeh-Nasiraie; Mohammad Shokrzadeh; Azade Ghorbani-HasanSaraei; Shahram Naghizadeh-Raeisi (Mazandaran University of Medical Sciences, 2020)
Background and Purpose: Aflatoxin B1 is one of the main poisonous substances in certain kinds of fungi all over the world. The toxin is a serious health threat to humans and livestock, particularly via DNA damage, and induces multiple cancers. Probiotic agents have confirmed positive beneficial effects in DNA protection against various toxic compounds. In this regard, the present study aimed to investigate the bio-protective effects of a native Lactobacillus plantarum subsp. plantarumNIMBB003 strain isolated from Iranian one-humped camel milk against AflatoxinB1 (AFB1)-induced genotoxicity damage, based on the micronucleus test as a genotoxicity monitoring method. Materials and Methods: In this study, a human male blood sample was treated and incubated with107, 109, and 1011CFU/mL of viable L. plantarum and IC50 dose ofAFB1alone and in combination. Afterward, assessed the rate of production of the micronucleus in bi-nucleated lymphocytes. It must be noted that a p-value of less than0.05 was considered significantly significant. Results: Based on the findings, the combined treatment of the L. plantarum at 1011 and109CFU/mL dose with 5.33±0.57% of the micronuclei fragments had protective effects and significantly decreased the genotoxicity of AFB1 by 76%. Conclusion: According to the findings, it can be concluded that L. plantarum in 109 CFU/mL had high protective potency against AFB1 genotoxicity. Consequently, the use of local, natural, and native protected compounds with antioxidant effects, such as probiotics agents, is one of the objectives of developing a green strategy in macro-management policies for the discovery and production of new medicines and functional foods with protective/therapeutic effects against nutritional and endogenous DNA toxins